2011
DOI: 10.1177/0273475311410852
|View full text |Cite
|
Sign up to set email alerts
|

Learning by Tweeting

Abstract: Marketing professionals use Twitter extensively for communicating with and monitoring customers, for observing competitors, and for analyzing chatter concerning brands, products, and company image. Can professors use Twitter to engage students in conversation about a marketing course? The authors argue that Twitter has many benefits for marketing educators who are interested in engaging students in experiential learning. In a real-time environment for student learning, professors may use Twitter for direct com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(73 citation statements)
references
References 11 publications
2
64
0
7
Order By: Relevance
“…When presented with Twitter messages that were half social and half professional, the students who tweeted more frequently (more than a few times per week) rated these hypothetical instructors as more credible than did students who tweeted less frequently. This finding adds to work by Rinaldo et al (2011), suggesting that students who are more familiar with Twitter may have positive experiences using the technology. We emphasize caution in the interpretation of this finding because it only emerged in one of the three conditions.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…When presented with Twitter messages that were half social and half professional, the students who tweeted more frequently (more than a few times per week) rated these hypothetical instructors as more credible than did students who tweeted less frequently. This finding adds to work by Rinaldo et al (2011), suggesting that students who are more familiar with Twitter may have positive experiences using the technology. We emphasize caution in the interpretation of this finding because it only emerged in one of the three conditions.…”
Section: Discussionsupporting
confidence: 51%
“…Rinaldo, Tapp, and Laverie (2011) found that students who utilized Twitter the most frequently benefited more in terms of increased student involvement in the course, increased satisfaction with the course, enhanced learning, and career preparation. Conversely, the students who were unfamiliar with Twitter resisted using it for class, complained that it was difficult to understand, and felt that it was a waste of time.…”
Section: Potential Impacts Of Social Media Usementioning
confidence: 99%
“…Ebner et al (2010) junto a Stieger y Burger (2010) reconocen que es útil en el ámbito universitario para difundir información y fomentar debates entre estudiantes interesados en temas específicos (Rinaldo, Tapp y Laverie, 2011). Favorece el aprendizaje a partir de la participación de la comunidad (Rampai y Sopeerak, 2011) y potencia el intercambio de opiniones y experiencias enriquecedoras entre personas de diversos grupos y proyectos (Rinaldo et al, 2011). Los hashtags permiten transmitir en tiempo real conferencias, seminarios, etc., realizar encuestas y formular preguntas directas a los ponentes.…”
unclassified
“…Twitter can also help to establish scholars' profiles and expertise through giving them a digital presence Veletsianos 2011). Meanwhile, a number of studies have reported on students' learning experiences with microblogging and social media (Dunlap and Lowenthal 2009;Greenhow and Robelia 2009;Junco et al 2011;Rinaldo et al 2011;Selwyn 2009Selwyn , 2012. The characteristics of interaction in Twitter align with constructivist and participatory pedagogies.…”
Section: Literature Reviewmentioning
confidence: 99%